2019
DOI: 10.1016/j.molp.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

DELLA and EDS1 Form a Feedback Regulatory Module to Fine-Tune Plant Growth–Defense Tradeoff in Arabidopsis

Abstract: Plants maintain a dynamic balance between growth and defense , and optimize allocation of resources for survival under constant pathogen infections. However, the underlying molecular regulatory mechanisms, especially in response to biotrophic bacterial infection, remain elusive. Here, we demonstrate that DELLA proteins and EDS1, an essential resistance regulator, form a central module modulating plant growth-defense tradeoffs via direct interaction. When infected by Pst DC3000, EDS1 rapidly promotes salicylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 48 publications
6
45
0
Order By: Relevance
“…AtRGL1 and AtRGL2 are involved in modulating leaf senescence, male sterility, and seed germination [23,24]. While AtRGL3 has been reported to contribute plant defense in response to biotic stresses [10,26,71]. Consistent with this, our qRT-PCR and predicted RNA-Seq data (Table S4.1) indicated that the individual BnDELLA gene subfamily exhibits signi cant varied expression and response to biotic and abiotic stress.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…AtRGL1 and AtRGL2 are involved in modulating leaf senescence, male sterility, and seed germination [23,24]. While AtRGL3 has been reported to contribute plant defense in response to biotic stresses [10,26,71]. Consistent with this, our qRT-PCR and predicted RNA-Seq data (Table S4.1) indicated that the individual BnDELLA gene subfamily exhibits signi cant varied expression and response to biotic and abiotic stress.…”
Section: Discussionsupporting
confidence: 82%
“…In recent years, the cultivation of the B. napus declining due to the versatility of the environment. DELLAs are well known as the master negative coregulators to mediate cross-talk between GAs and multiple hormonal signals to modulate plant growth and survival tradeoff, responding to abiotic and biotic conditions [8,10]. Previous reports on seeded plants had identi ed 1, 2, and 5 DELLA genes in Oryza sativa [16], Pisum sativum [18], and A. thaliana, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, rice black‐streaked dwarf virus regulates the GA‐signaling pathway via the interaction of the virus‐encoded P7‐2 and the plant’s GA‐insensitive dwarf2 (GID2) protein, which is an important component of GA signaling that dictates the degradation of DELLA proteins (Tao et al ., 2017). DELLAs are critical regulatory proteins that help to mediate crosstalk of GA with the JA‐ and SA‐signaling pathways, which is essential for balancing growth and defense (Navarro et al ., 2008; Y. Li et al ., 2019).…”
Section: Effects Of Virus Infection On Phytohormones Other Than Ja Smentioning
confidence: 99%